Destination Competitiveness: Amazing Bangkok versus Lion City Singapore - Adarsh Batra (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
To achieve bigger share of international tourists’ arrivals has led to growing intense competition between destinations. A comparison of tourism competitiveness between two popular tourism destinations, Bangkok and Singapore could be of interest to tourism planners and practitioners and research on it. This study aims to investigate and compare the competitiveness of Bangkok and Singapore cities as tourist destinations by examining tourism standing, contemporary tourism marketing strategies and their available features and benefits for arriving tourists. The research methodology is a qualitative interpretative approach, employing structured interviews and participant observation. Content analysis and constant comparison are applied to analyse the data. The emerging findings look at issues and perspectives related to how national tourism organizations and marketers can effectively apply tourism marketing strategies.